Adipocytokines visfatin and resistin in breast cancer: Clinical relevance, biological mechanisms, and therapeutic potential. (1st February 2021) - Wang, Yen-Yun; Hung, Amos C.; Lo, Steven; Yuan, Shyng-Shiou F.
Abstract: Obesity is one of the major modifiable risk factors in breast cancer, with obese adipose tissue showing a pathological role in breast cancer development and malignancy via the release of secretory factors, such as proinflammatory cytokines and adipocytokines. The current article focuses on visfatin and resistin, two such adipocytokines that have emerged over the last two decades as leading breast cancer promoting factors in obesity. The clinical association of circulating visfatin and resistin with breast cancer and their biological mechanisms are reviewed, in addition to their role in the context of tumor-stromal interactions in the breast cancer microenvironment. Recent findings have unraveled several mediators of visfatin and resistin that are involved in the crosstalk between breast cancer cells and adipose tissue in the breast tumor microenvironment, including growth differentiation factor 15 (GDF15), interleukin 6 (IL-6), and toll-like receptor 4 (TLR4). Finally, current therapeutics targeting visfatin and resistin and their respective pathways are discussed, including future therapeutic strategies such as new drug design or neutralizing peptides that target extracellular visfatin or resistin. These hold promise in the development of novel breast cancer therapies and are of increasing relevance as the prevalence of obesity-related breast cancer increases worldwide. Highlights: Elevated levels of circulating visfatin and resistin are associated with breast cancer progression. Extracellular visfatin and resistin promote breast tumor growth and metastasis. Adipose tissue interacts with breast cancer cells in the tumor microenvironment via secretion of visfatin and resistin. Visfatin and resistin may represent novel therapeutic targets for the treatment of breast cancer.